Meningkatkan Kemampuan Matematis Siswa Melalui Pengembangan LKS Berbantuan Wayground dalam Pembelajaran Cheerful Inquiry - Kurniati, Nia; Luritawaty, Irena Puji; Sumartini, Tina Sri (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study focuses on the development of Student Worksheets assisted by Wayground, which are utilized as supporting media in Cheerful Inquiry learning to improve junior high school students’ mathematical communication skills. The research method employed was Research and Development (R&D) using the ADII model. The research subjects consisted of 10 students from one junior high school in Garut Regency. The feasibility of the product was evaluated by media experts and material experts, as well as through small-group, medium-group, and large-group trials. The results of expert evaluations indicate that the design of the Wayground-assisted interactive worksheets falls into the good to very good category, with user assessment scores exceeding 80. The effectiveness test shows an N-Gain value of 0.81, which is classified as high. This indicates that the developed Wayground-supported student worksheets are effective in improving students’ mathematical communication skills. This media provides opportunities for students to develop mathematical communication skills through writing, drawing, and expressing mathematical concepts, while also creating an enjoyable and relatively conducive learning environment. Based on the research findings, the developed Wayground-assisted student worksheets are declared feasible for use in mathematics learning.   Keywords: Wayground; Cheerful Inquiry; Student Worksheets; Mathematical Communication Skills